All aboard! Skills for new jobs in unmanned automated vehicle industries - Aguiar, B.; Rosa, M.; Pinto, M.; Maio, C. (Farnborough International Airshow 2022, 2022)
Unmanned Automated Vehicles (UAVs) have entered our sky, and in a near future, it is expected that we will live in a U-Space where mixed traffic operates, and space is explored resorting to UAVs. This is only possible due to the technological disruption of Industry 4.0, and the consequential implementation of more complex automated systems. Automation is permeating other sectors interacting with aviation, with consequences for human-machine interface, which, if not addressed, may negatively impact the workforce and the market. Recent data from the EU funded project “Skill-UP” (2021) regarding UAVs showed that the success of these transitions relies on training and skilling the workforce - remote pilot operators (RPAs). Both survey and interview data showed that behavioral skills training was deemed essential to the adaptation to the future work scenario. RPAs interviewed – which included employees, trainers, and employers – pointed out the importance of skills such as decision making, teamwork/collaboration, and emotion management. RPA’s will be more accountable for monitoring and intervene in complex and/or unpredictable situations, which will require fast and accurate decision-making. These are important lessons to be taken into account in crafting new jobs like these, also considering how they can operate in synergy with other sectors sharing similar challenges and demands, such as space and maritime. Therefore, in line with the EU Pact for Skills in industry, we bring forward the idea to invest in skilling the future workforce for this promising field. Innovation that considers multiple angles (e.g. technological, human) will be more impactful than a purely technological approach, while providing important insights for managing the human side of technological disruption.